TATA Binding Protein Can Stimulate Core-Directed Transcription by Yeast RNA Polymerase I - Aprikian, Pavel (American Society for Microbiology, 2000)
The TATA binding protein (TBP) interacts with two transcription factor complexes, upstream activating factor (UAF) and core factor (CF), to direct transcription by RNA polymerase I (polI) in the yeast Saccharomyces cerevisiae. Previous work indicates that one function of TBP is to serve as a bridge, ennabling UAF to recruit and stabilize the binding of CF (23, 24). In this work we show that, in addition to aiding recruitment, TBP also directly aids CF function. Overexpression of TBP in strains with UAF components deleted will stimulate CF-directed transcription nearly to wild-type levels in vivo. In vitro, increasing the concentration of TBP stimulates CF-directed transcription in the absence of either UAF or its DNA binding site. This dual function of TBP, serving as a critical member of a core promoter complex as well as a contact point for upstream activators, appears similar to the dual roles that TBP also plays in transcription by RNA polII.